USING PANEL DATA TO ANALYZE THE IMPACT OF TRADE OPENNESS ON ECONOMIC GROWTH IN THE GCC (1970-2017) - محسن الزوبعي, عبيد محمود; عبد الكاظم اليساري, حاتم هاتف (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
Statistical data play an important role in analyzing the different phenomena in the human societies, especially the economic phenomenon which focus on macroeconomic issues. The results of this type of studies provide valuable information for the decision makers in the political and economic aspects. Type of data available for the researcher determines the econometric model, which should be used. One type of the data is the panel data. This study employ regression panel data as well as FMOLS and DOLS. This study is an attempt to study the impact of trade openness on economic growth in the countries of the GCC, during the period 1970-2017. The main findings of the study are that trade openness is the most important factor in economic growth, followed by labor input. The most important recommendations that can be raised is the need to implement policies that can enhance trade openness and pay attention to the training of workers and expand the current employment policies. The results also suggest that investment allocation should be done in more effective way.